Influência da maltodextrina, goma arábica e dextrina sobre o pó da polpa de Pitaia vermelha Hylocereus polyrhizus liofilizada - Alves, Thallyne de Brito (2021)
The objective of this research was to evaluate the influence of maltodextrin, gum arabic and dextrin on the physical and physicalchemical characteristics of the red pitaya pulp powder obtained by the freeze-drying process. They were determined as physicalchemical characteristics of the pulp. The best powder characteristics were chosen from the experimental design of simplex- centroid- mixtures. The response variables were hygroscopicity, solubility, moisture content, flow index, Carr index and the Hausner ratio. The influence of the three adjuvants was also evaluated through morphological analysis and sorption isotherms. The powder in the best condition was chosen physically and chemically and its stability was analyzed for 60 days. The pulp of pitaya showed a high moisture content, 107.02 mg/100g of ascorbic acid, 111.17 mg EAG/100g of total phenolic compounds and 11.43 mg/100g of betalains, low levels of acidity and soluble solids. The powders showed hygroscopicity between 6.55 and 10.37%, moisture between 3.17 and 4.78% and solubility between 91.74 and 96.69%, flow index between 3.44 to 4.43, Carr index between 22.61 to 43.00% and the Hausner ratio between 1.29 to 1.75. The reduction of Carr index parameters and the Hausner ratio of the samples was observed with the increase in the concentration of maltodextrin and decrease in the dextrin and gum arabic in the mixture. The increase in dextrin in the mixture contributed to the reduction of moisture in powders, while the increase in gum arabic resulted in powders with greater hygroscopicity The flow indexes showed that the powder containing only maltodextrin is classified as easy to flow (4.11) and those containing only gum arabic or dextrin as cohesive (3.44 and 3.54). The powder with maltodextrin had a higher densities (469,6 a 595,1 kg/m3) and the powder with gum arabic has lower wall friction angles (10,5 a 10,7º). In the morphological evaluation was observed irregularly shaped powders and different behaviors in according to the adjuvantes, surfaces more rounded and more agglomerated with maltodextrin. For the adsorption isotherms of powders, the best fit model was the BET model with estimated average errors of 2.78%, with the dextrin being more stable at temperatures of 25 and 40 °C due to its lower equilibrium moisture. Among the adjuvants used, a maltodextrin was the one that most contributed to the better fluidity and flowability of the pitaya pulp powder. The lyophilization process resulted in variations in the physicochemical results of the powders. The study of the stability of the pitaya pulp powder allowed to observe the decrease of the phenolic compounds, betalaines and pH from the 15th day of storage and maintained a moisture, hygroscopicity and acidity.